2018
DOI: 10.1103/physrevmaterials.2.096001
|View full text |Cite
|
Sign up to set email alerts
|

Vaporlike phase of amorphous SiO2 is not a prerequisite for the core/shell ion tracks or ion shaping

Abstract: When a swift heavy ion (SHI) penetrates amorphous SiO 2 , a core/shell (C/S) ion track is formed, which consists of a lower-density core and a higher-density shell. According to the conventional inelastic thermal spike (iTS) model represented by a pair of coupled heat equations, the C/S tracks are believed to form via "vaporization" and melting of the SiO 2 induced by SHI (V-M model). However, the model does not describe what the vaporization in confined ion-track geometry with a condensed matter density is. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…evaluated amorphous SiO 2 by small angle X-ray scattering (SAXS) and reported the total track diameters of ~10 nm for low velocity and ~8 nm for high velocity, respectively 28 . It should be noted that tracks in amorphous SiO 2 have core/shell structures 15 , which is different from the hard-cylinder-type of crystalline SiO 2 30 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…evaluated amorphous SiO 2 by small angle X-ray scattering (SAXS) and reported the total track diameters of ~10 nm for low velocity and ~8 nm for high velocity, respectively 28 . It should be noted that tracks in amorphous SiO 2 have core/shell structures 15 , which is different from the hard-cylinder-type of crystalline SiO 2 30 .…”
Section: Discussionmentioning
confidence: 93%
“…Although the mechanism of NP shape elongation induced by SHIs is yet to be identified, a majority of researchers agree with the importance of the ion-track formation in matrix materials 415 . However, the tracks cannot be directly observed by TEM in amorphous matrices 28 , except in a very thin self-standing film 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process leads to the formation of a local temperature spike at the metal/dielectric boundary where very high temperatures can be reached. This may explain the low energy threshold observed for ion shaping of ~4 keV/nm in a-SiO2 [48]. As a consequence, the ion-shaping process can take place if the anisotropic thermal profile around the metal/dielectric boundary surpasses the melting temperature of the surrounding medium, and the efficiency is linked to the duration of this process, which is affected by the thermal conductivity of the surrounding medium.…”
Section: Competing Processes At the Amorphous Silicon Nitride/silicon Dioxide Interfacementioning
confidence: 99%
“…[ 74 ] To date, there are two major mechanisms proposed for the elongation: a) synergy effects by ion hammering and NP melting, [ 75–82 ] and b) ion shaping by ion tracks. [ 83–88 ] Ion hammering was discovered by Klaumunzer in 1983 that the NP dimensions grow (shrink) perpendicular (parallel) to the ion beam direction, which has been well understood by effective‐flow temperature approach. [ 89 ] In 2003, D'Orleans et al observed the ion shaping that spherical NPs become prolate with major axis oriented parallel to the incident direction.…”
Section: Ion Beam Synthesis Of Nanoparticlesmentioning
confidence: 99%